2, 7-substituted fluorenone-based liquid crystal trimers: twist-bend nematic phase induced by outer thioether linkage. (3rd April 2022) - Arakawa, Yuki; Komatsu, Kenta; Tsuji, Hideto
ABSTRACT: 2, 7-Substituted fluorenone has a planar and slightly bent aromatic structure and is used as a building block for organic liquid crystals (LCs). Herein, we report for the first time the synthesis, phase-transition behaviour, and mesophase structure of fluorenone-incorporated LC trimers that exhibit an emerging helical twist-bend nematic (NTB ) phase. The LC trimers possess a central 2, 7-ether-substituted fluorenone and bilateral cyanobiphenyl groups linked via odd alkylene C n H2 n spacers ( n  = 7 or 9) with either ether or thioether outer linkages; these are abbreviated CBO n OFlnO n OCB and CBS n OFlnO n SCB, respectively. The CBO n OFlnO n OCB trimers having only ether linkages display only the conventional nematic (N) phase, whereas the outer thioether-linked CBS n OFlnO n SCB trimers form an NTB phase below the temperature range of the N phase. Furthermore, the phase-transition behaviour of these fluorenone-based LC trimers is compared with that of the corresponding all-biphenyl-based motif trimer analogues, CBO n OBO n OCB and CBS n OBO n SCB.